David and Goliath [compact disc, unabridged] : underdogs, misfits, and the art of battling giants - Gladwell, Malcolm, 1963- (Hachette Audio, 2013)
Malcolm Gladwell, with his unparalleled ability to grasp connections others miss, uncovers the hidden rules that shape the balance between the weak and the mighty, the powerful and the dispossessed.